Optimizing Antitumor Effect of Triple-Negative Breast Cancer via Rosmarinic Acid–β-Cyclodextrin Inclusion Complex - Yuan Li; Muhammad Inam; Muhammad Waqqas Hasan; Kaixin Chen; Zhongqian Zhang; Yongcheng Zhu; Jiayu Huang; Zhuowen Wu; Wenjie Chen; Min Li (Pharmaceutics)
Background: Rosmarinic acid (ROS) has gained notable attention for its anticancer potential; however, its limited aqueous solubility hinders its effective delivery and application in pharmaceutical formulations. Methods: To overcome this limitation, an inclusion complex of ROS with β-cyclodextrin (β-CD) was prepared using the recrystallization method. The resultant ROS–β-CD complex was comprehensively characterized by powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). Results: The ROS–β-CD complex showed a significant improvement in the solubility and dissolution profile of ROS, underscoring its potential for enhanced bioavailability and therapeutic efficacy in pharmaceutical applications. In vitro assays were performed to assess the effects on cell viability, proliferation, apoptotic pathways, and 3D spheroid tumor models. Conclusions: The results demonstrated that ROS–β-CD exhibited superior anticancer properties compared to free ROS, effectively reducing the viability and proliferation of the MD-MBA-231 cell line and inducing apoptosis. This research signifies a substantial advancement in developing therapeutic strategies for TNBC, leveraging the distinct properties of the ROS–β-CD inclusion complex.